2013
DOI: 10.1902/jop.2012.120508
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Liposomal Lactoferrin Inhibits Inflammation‐Related Bone Breakdown Without Interrupting Orthodontic Tooth Movement

Abstract: Orally administered LbLF significantly inhibits LPS-induced alveolar bone resorption but not OF-induced bone remodeling. LbLF could be a potent therapeutic and preventive agent to control periodontal inflammation in patients undergoing orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…A previous study has shown that chronic alcohol intoxication decreases salivary lactoferrin output (Waszkiewicz et al, 2012). Though it has been demonstrated that orally administered liposomal lactoferrin inhibits LPS-induced alveolar bone resorption (Kawazoe et al, 2012), until now there are no direct reports on lactoferrin changes in the saliva after LPS infection as far as we know. This study firstly demonstrates that the salivary lactoferrin content decreases after LPS challenge.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study has shown that chronic alcohol intoxication decreases salivary lactoferrin output (Waszkiewicz et al, 2012). Though it has been demonstrated that orally administered liposomal lactoferrin inhibits LPS-induced alveolar bone resorption (Kawazoe et al, 2012), until now there are no direct reports on lactoferrin changes in the saliva after LPS infection as far as we know. This study firstly demonstrates that the salivary lactoferrin content decreases after LPS challenge.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the present study demonstrate that LbLF inhibits the LPS-induced upregulation of TNF-α mRNA expression. In our previous study, it was revealed that orally administered LbLF significantly inhibits LPS-induced alveolar bone resorption ( 28 ). We also previously demonstrated the anti-inflammatory effect of LF ( 29 ), and other studies have observed that LF may interact with epithelial and immune cells in the intestinal mucosa ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of using mice as a model include the considerable background information on their biological system, a wide range of genetically engineered strains (e.g., gene knockouts for key receptors or signaling molecules) and availability of high‐quality chemical reagents . Although numerous animal studies have been carried out to investigate OF on periodontal cellular responses and bone loss under physiological conditions , only a few animal studies involving orthodontic treatment in the context of periodontal disease were performed, and most of them were performed in rats but not mice , presumably due to the technical challenges having to do with the relatively small size of the teeth and oral cavity of the mouse. To our knowledge, this is the first time a mouse model was established to investigate the potential mechanism of OF‐exacerbated PBL in experimental periodontitis.…”
Section: Discussionmentioning
confidence: 99%